Case study of liquid suction heat exchanger in a mechanical refrigeration system using alternative refrigerants - Ahmed Mahmood, Raid (International Journal of Engineering and Technology, 2020)
This paper investigates the effect of adding a liquid-suction heat exchanger on the performance of a mechanical refrigeration system using alternative refrigerants. Engineering Equation Solver (EES) was used to simulate a mechanical refrigeration system in two configurations: modified system with liquid-suction heat exchanger and system without liquid-suction heat exchanger. The results revealed that the liquid-suction heat exchanger has a significant effect on the system performance as it influences the subcooling and superheating temperatures. The results also showed that the highest value of the coefficient of performance (COP) was achieved by the modified system with refrigerant type R134a, COP was about 7% and 12% higher than that of refrigerants R600a and R22 respectively. It also presented that R600a has high response to increase the refrigerant effect when the liquid-suction heat exchanger is used. R600a is good alternative refrigerant and it can be used in the mechanical refrigeration system, but its COP is lower than that of R134a.Â Â